Peran Teknologi dalam Pengembangan Bahasa Inggris di Desa Ngrowo melalui Metode Drilling dan Repetition - Arihakam, Beny (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2023)
The purpose of This research is to determine the role of technology in the process of improving English speaking skills in Ngrowo village using the drilling and repetition method. Technology has an extraordinary role in developing villages, especially the English tourist village in Ngrowo village. Learning that is really liked byThese students are learning English followed by supporting technologyso it makes it easierlearnersinteract. The drilling and repetition method is one way to quickly master English. The research uses action research. The data collection process is observation, daily notes, documentation and tests. The research data validation process is carried out during the process of action activities and results obtained and involves collaborators. The research results show that the role of technology in the process of improving English speaking skills has a positive impact on improving English speaking skills in Ngrowo village. This is because the application of drilling and repetition methods which are easy to understand is very enjoyable. The impact of Ngrowo village is that more and more students are taking part in English language development activities. Initially there were only 50 participants, growing to 150 children from various villages taking part in English language development activities.